The problem of physics learning: The effort to increase the interest and learning result of Newton laws - Tomy Suganda; Endang Purwaningsih; Parno Parno (Berkala Fisika Indonesia : Jurnal Ilmiah Fisika, Pembelajaran dan Aplikasinya, 2021)
This study aimed to identify the problems and solutions of physics learning on the concept of newton's law of motion. The researcher used a qualitative descriptive study with a sample of students and physics teachers at Islamic Senior High School or Madrasah Aliyah in Malang. The data was collected through interviews and observations during two meetings. The first meeting was an interview section with the teachers to identify the problems in physics learning. The second meeting was the student observations for further investigation based on the findings from the interview data. This present study was designed for solving physics learning problems on the concept of newton's law of motion. The result showed that classroom learning still utilises a teacher-centred approach, resulting in poor interactive responses and learning outcomes. Besides, The school does not support enough facilities, such as learning equipment and laboratories. Therefore, teaching aids can improve the students' quality and quantity on learning the concept of newton's law of motion.